Evaluation of endodontic work in Mosul city - Abdul-Adheem R Al-Mallah; Ragheed M Basheer; Raid M Basheer (University of Mosul, College of Dentistry, 2007)
Aims: To evaluate different steps of endodontic procedures done by the dentists in Mosul city. Materials and Methods: A dental questionnaire sheet that consisted of 21 questions regarding numerous steps of endodontics starting from pre-operative (diagnostic) phase to post-operative (final restoration) phase was distributed randomly to 150 dentists working in Mosul city. The dentists involved in the study were both specialists and non-specialists. Then, the sheets were collected and the data analyzed. Results: Revealed that there was a difference in performing specific steps of endodontics between the dentists. In some questions there was no great difference between specialists and non-specialists, but in other procedures, a great difference could be observed. This difference was not only between specialists and non-specialists groups, but also inside these groups as well. Conclusions: The dentists in Mosul city generally lack information about some important steps in endodontic work that may affect negatively the outcome of the procedure as a whole. This deficiency can be compensated for by holding continuous education programs in addition to the dentists' responsibility in staying in contact with the most modern advancements in different fields of dentistry.